Assembling things right. The material dimensions of West German diplomacy (1950s to 1970s) - Derix, Simone (Walter de Gruyter GmbH, 2016)
This article investigates the material dimensions of international relations by analysing West German diplomacy after 1945. First, it focuses on the meaning of individual objects in communications and encounters between two states. Second, diplomatic practices are understood as attempts to create and shape specific atmospheres, as assemblages involving various objects, persons and practices. Diplomacy is thereby emphasised as a construct repeatedly connected to the material. Third, at the meta-level, individual diplomatic objects and assemblages are embedded in an international system of materiality. It is argued that the material participates in the construction of international regimes of perception. Overall, the different material dimensions make it evident that objects are fundamentally involved in the history of relationships between states - at the micro-level (individual objects), at the meso-level (assemblages) and at the meta-level (patterns of systems).
CRIS-Team Scopus Importer:2023-03-21